Treatment of Comorbid Obesity and Major Depressive Disorder: A Prospective Pilot Study for their Combined Treatment - Lucy F. Faulconbridge; Thomas A. Wadden; Robert I. Berkowitz; Melissa E. Pulcini; Thomas Treadwell (Journal of Obesity)
Background. Obese individuals who suffer from major depressive disorder are routinely screened out of weight loss trials. Treatments targeting obesity and depression concurrently have not been tested. Purpose. To test the short-term efficacy of a treatment that combined behavioral weight management and cognitive behavioral therapy (CBT) for obese adults with depression. Methods. Twelve obese females diagnosed with major depressive disorder received weekly group behavioral weight management, combined with CBT for depression, for 16 weeks. Weight, symptoms of depression, and cardiovascular disease (CVD) risk factors were measured at baseline and week 16. Results. Participants lost 11.4% of initial weight and achieved significant improvements in symptoms of depression and CVD risk factors. Conclusions. Obese individuals suffering from major depressive disorder can lose weight and achieve improvements in symptoms of depression and CVD risk factors with 16 weeks of combined treatment. A larger randomized controlled trial is needed to establish the efficacy of this treatment.